DECENTRALIZATION AND LEGAL FRAGMENTATION: GOVERNANCE CHALLENGES IN THE POST-REFORM ERA - Yusdiyanto Yusdiyanto; Tatiana Epifanova (Diponegoro Law Review, 2026)
Post-reform decentralization in Indonesia has become pivotal for reinforcing democracy and improving governance. Implementation over two decades has led to serious problems, particularly legal fragmentation and regional governance disparities. In this article, we aim to explore the relationship between decentralization and legal fragmentation, and its implications for governance in the post-reform era. To this end, we use a combination of doctrinal and non-doctrinal approaches, with the primary emphasis remaining on the doctrinal method. Analysis, including national regulations, court decisions, government reports, and national and international academic research. The results highlight three main findings. First, decentralization has successfully nurtured local democratization through direct regional head elections and increased public participation, even though the practice of money politics and the dominance of local elites continue to pose challenges. Second, regional autonomy has resulted in legal fragmentation, marked by thousands of problematic regional regulations, either revoked for conflicting with higher-level regulations or for being discriminatory and impeding investment. Third, governance faces multidimensional challenges, including weak institutional capacity, a tug-of-war over central and regional authority, and corruption in several regions. This research provides a critical analysis of the dynamics of decentralization in Indonesia, underscoring the urgency of legal harmonization, institutional design, and regional government capacity. Accordingly, decentralization does not only symbolize democratization but can also be instrumental for strengthening legal certainty and governance.